Transatlantic Trends Survey, 2004 - Kennedy, Craig ([Verlag nicht ermittelbar], 2005)
The Transatlantic Trends Survey, conducted June 6-26, 2004, was designed to assess respondents' opinions on their own and other countries' involvement in world affairs and events. The survey was administered to a sample of the population, 18 years and older, in France, Germany, Great Britain (with the exception of Northern Ireland), Italy, The Netherlands, Poland, Portugal, Slovakia, Spain, Turkey, and the United States. Respondents were asked to give their opinions on the state of relations between the United States and the European Union (EU) particularly as they relate to issues of leadership and cooperation with respect to the War in Iraq, the larger war against international terrorism, and international security. Respondents were asked whether they preferred strong American leadership or a more dominant leadership role for the EU and whether they thought these issues had worked to draw the United States and the EU closer or distance them further. Respondents were also asked to evaluate the foreign policy decisions implemented by American president, George W. Bush. Respondents were asked what effects they thought the War in Iraq was having on terrorism and if the war had been worth it or not. Respondents were also asked how they would feel if their country was to withdraw troops or if withdrawn troops were to be sent back to Iraq. The survey then asked respondents for their opinion, more generally, on the use of military force and under what circumstances they would favor military intervention. The survey also sought to decipher whether respondents approved of unilateral military action or only if military action was sanctioned by their countries' allies, NATO, or the United Nations (UN). The survey also sought the respondents' opinions on a wide variety of other issues such as immigration, the AIDS epidemic in Africa, the Arab/Israeli conflict, Islamic fundamentalism, the international role of the UN, and the advantages and disadvantages to Turkey's admittance into the European Union. The survey also sought to obtain information regarding the respondents' political tendencies and party preferences. Finally, the survey attempted to identify the issues most important to the respondents. The data also includes several demographic variables that captured information regarding the respondents' sex, age, level of education, occupation, household size, region, and ethnicity (United States only).